Identificação das intervenções usadas por fisioterapeutas brasileiros no tratamento da dor patelofemoral - Pisani, Giulia Keppe (2021)
Patellofemoral pain (PFP) is a condition that has an insidious onset and is characterized by peri- or retro-patellar pain, which is aggravated by activities that increase stress on the patellofemoral joint, with a prevalence of 22.7% in the general population. Currently, there are consensuses and clinical practice guides for the physical therapy treatment of this disorder, which are periodically updated in order to bring the best evidence of methods and practices available in the literature. However, it is not known whether the interventions most commonly used by Brazilian physical therapists in the treatment of PFP are in accordance with the best available evidence. Therefore, the objectives of this dissertation were: 1- to identify which interventions are most commonly used by Brazilian physical therapists in the rehabilitation of PFP and verify if the interventions used are in accordance with current scientific evidence; 2- check whether some characteristics of the sample and information on Evidence-Based Practice (EBP) influence the choice of interventions used by physical therapists. Brazilian physiotherapists registered with the Federal Council of Physiotherapy and Occupational Therapy (COFITO) and with previous experience in caring for patients with PFP were included in this study. Data on sample characteristics, information on EBP and interventions used in the treatment of PFP were collected through an online questionnaire, disseminated via social networks. In addition to a descriptive analysis of the data, a logistic regression analysis was applied to verify the association of interventions with some characteristics of the sample and information about EBP. One hundred and ninety-four physical therapists answered the questionnaire. Of the recommended interventions, 97.4% of respondents reported using the combined hip and quadriceps muscle strengthening exercises, but only 25.3% used foot orthoses. A significant number of physical therapists also reported using interventions that are not recommended (such as patellar mobilization; mobilization/manipulation of the knee, lumbar and hip; and electrothermophototherapy resources). Physiotherapists who completed a master's or doctoral degree and who know/heard about clinical practice guides or guidelines are 2.57 and 3.81 times more likely, respectively, to use recommended interventions. We conclude that most Brazilian physical therapists opt for interventions that are in line with current scientific evidence. However, a significant number of them also use non-recommended interventions for the treatment of PFP.